Gambaran Pengetahuan, Sikap, dan Praktik Perilaku Mahasiswa terhadap HIV/AIDS dan ODHA (Orang dengan HIV/AIDS) - Bona S. H. Hutahaean (Jurnal Ilmiah Psikologi MIND SET, 2017)
Undergraduate students in adolescence and young adulthood period are sexually productive. It is crucial to discover their knowledge, attitude, and practice (KAP) towards HIV/AIDS since the highest HIV infection in Indonesia until 2016 is between those ages. The survey was conducted in Indonesia between November-December 2015. Data was collected using online structured KAP questionnaire to 350 undergraduate students (aged 18-23 years old) in Universitas Indonesia and analyzed with descriptive statistic. The KAP questionnaire used was adapted from Mulu, Abera, and Yinner (2014). Results shown that most participants answered correctly in knowledge items, but most of them still didn't know that HIV and AIDS are two different things, and they think that HIV can be infected through sharing foods, exchanging clothes and toilets with PLWH (People Living with HIV). Most participants have a positive attitude towards HIV/AIDS, but they have a negative attitude regarding on using condom while having sex as an affront to the couple, and disagreeing to live together with PLWH. Regarding on the practice, as much as 76 participants who have had sex ever had a risky sexual behavior but never had VCT (Voluntary Counseling & Testing), while the rest of participants who never had sex mostly have seen a condom but didn't feel comfortable to hold it. Knowledge towards HIV/AIDS was quite sufficient, the attitude was fair enough, but the practice for the participants who have had sex needed attention more. The results also might indicate stigma towards HIV/AIDS in Indonesia still exists because HIV is considered as an easily infected disease.